Polski reportaż a powieść drogi - Przemysław Pietrzak (Zagadnienia Rodzajów Literackich, 2024)
The following article concerns Polish reportage of 20th and 21st century. The discussion focuses on the elements of fiction genres transferred into a documentary form. One of such genres is what author calls a novel of the road. It comprises several kinds of old novel, like Greek and Roman adventure novels, Spanish, French and English rogue and picaresque novels, sentimental novels, some examples of chivalric romances with parody of Miguel de Cervantes. They can be divided into two variants: the one with the protagonist feeling strange in the space he travels through, and the other with the hero feeling a kinship with the surroundings (the latter is typical of the sentimental kind and some romantic poems based on the travel). A reportage usually consists of a mixture of both variants. It is discussed here by using examples taken from various periods in the history of Polish reportage: texts by Ksawery Pruszyński, Melchior Wańkowicz, Michał Choromański, Wanda Melcer, Ryszard Kapuściński, Krzysztof Kąkolewski, Jacek Hugo-Bader, Agnieszka Pajączkowska, and Michał Książek. The discussion concentrates on the fundamental features of those texts and contrasts them with the opposite model. What author particularly cares about are not only the formal differences, but also a specific worldview inscribed in reportage of the road, concerning subject, his or her knowledge, interrelations with the others, and setting in the world.